cat theory tweaks
[lambda.git] / advanced_topics / monads_in_category_theory.mdwn
index f05747f..588d1a3 100644 (file)
@@ -273,8 +273,8 @@ Summarizing then, the monad laws can be expressed as:
 
 
 
-The standard category-theory presentation of the monad laws
------------------------------------------------------------
+Getting to the standard category-theory presentation of the monad laws
+----------------------------------------------------------------------
 In category theory, the monad laws are usually stated in terms of `unit` and `join` instead of `unit` and `<=<`.
 
 <!--
@@ -308,7 +308,7 @@ Recall that `join` is a natural transformation from the (composite) functor `MM`
 Next, let <code>&gamma;</code> be a transformation from `G` to `MG'`, and
  consider the composite transformation <code>((join MG') -v- (MM &gamma;))</code>.
 
-*      <code>&gamma;</code> assigns elements `C1` in <b>C</b> a morphism <code>&gamma;\*: G(C1) &rarr; MG'(C1)</code>. <code>(MM &gamma;)</code> is a transformation that instead assigns `C1` the morphism <code>MM(&gamma;\*)</code>.
+*      <code>&gamma;</code> assigns elements `C1` in <b>C</b> a morphism <code>&gamma;\*:G(C1) &rarr; MG'(C1)</code>. <code>(MM &gamma;)</code> is a transformation that instead assigns `C1` the morphism <code>MM(&gamma;\*)</code>.
 
 *      `(join MG')` is a transformation from `MM(MG')` to `M(MG')` that assigns `C1` the morphism `join[MG'(C1)]`.
 
@@ -318,10 +318,10 @@ Composing them:
        (2) ((join MG') -v- (MM &gamma;)) assigns to C1 the morphism join[MG'(C1)] &#8728; MM(&gamma;*).
 </pre>
 
-Next:
+Next, consider the composite transformation <code>((M &gamma;) -v- (join G))</code>:
 
 <pre>
-       (3) Consider the composite transformation <code>((M &gamma;) -v- (join G))</code>. This assigns to C1 the morphism M(&gamma;*) &#8728; join[G(C1)].
+       (3) ((M &gamma;) -v- (join G)) assigns to C1 the morphism M(&gamma;*) &#8728; join[G(C1)].
 </pre>
 
 So for every element `C1` of <b>C</b>:
@@ -347,16 +347,16 @@ Next recall that `unit` is a natural transformation from `1C` to `M`. So for ele
        (4) unit[C2] &#8728; f = M(f) &#8728; unit[C1]
 </pre>
 
-Next:
+Next, consider the composite transformation <code>((M &gamma;) -v- (unit G))</code>:
 
 <pre>
-       (5) Consider the composite transformation ((M &gamma;) -v- (unit G)). This assigns to C1 the morphism M(&gamma;*) &#8728; unit[G(C1)].
+       (5) ((M &gamma;) -v- (unit G)) assigns to C1 the morphism M(&gamma;*) &#8728; unit[G(C1)].
 </pre>
 
-Next:
+Next, consider the composite transformation <code>((unit MG') -v- &gamma;)</code>:
 
 <pre>
-       (6) Consider the composite transformation ((unit MG') -v- &gamma;). This assigns to C1 the morphism unit[MG'(C1)] &#8728; &gamma;*.
+       (6) ((unit MG') -v- &gamma;) assigns to C1 the morphism unit[MG'(C1)] &#8728; &gamma;*.
 </pre>
 
 So for every element C1 of <b>C</b>:
@@ -379,39 +379,46 @@ So our **(lemma 2)** is:
 Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <code>&gamma; &lt;=&lt; &phi;</code> in the monad laws. For simplicity, I'll omit the "-v-".
 
 <pre>
-       for all &phi;,&gamma;,&rho; in T, where &phi; is a transformation from F to MF', &gamma; is a transformation from G to MG', R is a transformation from R to MR', and F'=G and G'=R:
+       For all &rho;, &gamma;, &phi; in T,
+       where &phi; is a transformation from F to MF',
+       &gamma; is a transformation from G to MG',
+       &rho; is a transformation from R to MR',
+       and F'=G and G'=R:
 
-       (i) &gamma; <=< &phi; etc are also in T
+            (i) &gamma; <=< &phi; etc are also in T
        ==>
-       (i') ((join G') (M &gamma;) &phi;) etc are also in T
+           (i') ((join G') (M &gamma;) &phi;) etc are also in T
 
 
-       (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
+
+           (ii) (&rho; <=< &gamma;) <=< &phi;  =  &rho; <=< (&gamma; <=< &phi;)
        ==>
-                (&rho; <=< &gamma;) is a transformation from G to MR', so:
-                       (&rho; <=< &gamma;) <=< &phi; becomes: (join R') (M (&rho; <=< &gamma;)) &phi;
-                                                       which is: (join R') (M ((join R') (M &rho;) &gamma;)) &phi;
-                       substituting in (ii), and helping ourselves to associativity on the rhs, we get:
+                   (&rho; <=< &gamma;) is a transformation from G to MR', so
+                       (&rho; <=< &gamma;) <=< &phi; becomes: ((join R') (M (&rho; <=< &gamma;)) &phi;)
+                                                       which is: ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;)
+
+                       similarly, &rho; <=< (&gamma; <=< &phi;) is:
+                                                       ((join R') (M &rho;) ((join G') (M &gamma;) &phi;))
 
-            ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                     ---------------------
+                       substituting these into (ii), and helping ourselves to associativity on the rhs, we get:
+               ((join R') (M ((join R') (M &rho;) &gamma;)) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+    
                        which by the distributivity of functors over composition, and helping ourselves to associativity on the lhs, yields:
-                    ------------------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
-                                                             ---------------
+               ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (M &rho;) (join G') (M &gamma;) &phi;)
+  
                        which by lemma 1, with &rho; a transformation from G' to MR', yields:
-                                                             -----------------
-            ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
+               ((join R') (M join R') (MM &rho;) (M &gamma;) &phi;) = ((join R') (join MR') (MM &rho;) (M &gamma;) &phi;)
 
-                       which will be true for all &rho;,&gamma;,&phi; just in case:
+                       which will be true for all &rho;,&gamma;,&phi; only when:
+               ((join R') (M join R')) = ((join R') (join MR')), for any R'.
 
-             ((join R') (M join R')) = ((join R') (join MR')), for any R'.
+                       which will in turn be true when:
+      (ii') (join (M join)) = (join (join M))
 
-                       which will in turn be true just in case:
-
-       (ii') (join (M join)) = (join (join M))
 
 
+        (iii.1) (unit G') <=< &gamma;  =  &gamma;
+                when &gamma; is a natural transformation from some FG' to MG'
        (iii.1) (unit F') <=< &phi;  =  &phi;
        ==>
                        (unit F') is a transformation from F' to MF', so:
@@ -429,6 +436,10 @@ Finally, we substitute <code>((join G') -v- (M &gamma;) -v- &phi;)</code> for <c
        (iii.1') (join (M unit) = the identity transformation
 
 
+
+
+        (iii.2)                     &gamma;  =  &gamma; <=< (unit G)
+                when &gamma; is a natural transformation from G to some MR'G
        (iii.2) &phi;  =  &phi; <=< (unit F)
        ==>
                        &phi; is a transformation from F to MF', so:
@@ -466,8 +477,8 @@ Collecting the results, our monad laws turn out in this format to be:
 
 
 
-7. The functional programming presentation of the monad laws
-------------------------------------------------------------
+Getting to the functional programming presentation of the monad laws
+--------------------------------------------------------------------
 In functional programming, unit is usually called "return" and the monad laws are usually stated in terms of return and an operation called "bind" which is interdefinable with <=< or with join.
 
 Additionally, whereas in category-theory one works "monomorphically", in functional programming one usually works with "polymorphic" functions.